التحليل الاقتصادي الرياضي لدور راس المال الطبيعي في النمو الزراعي المستدام - جميل, شيماء محمد نجيب (Sulaimani Journal for Humanities, 2021)
Relying on sustainable agriculture through the data of natural capital is necessary to maintain agriculture that serves the current and future generation, and to achieve the objective of the study, which is to preserve natural capital for its importance as a necessary commodity that is produced in the economy and has an economic value, and to work on investing and sustaining it without harming it or depleting it to achieve economic goals to meet The needs of community members economically and environmentally and to reach sustainable agriculture, as the study assumes (natural capital makes a real effective contribution to preserving the environment in addition to contributing to achieving sustainable agricultural development) and thus achieving sustainable agricultural growth, and based on the Cobb production function Douglas), which includes major factors (labor, capital) that have been developed based on contemporary economic ideas by adding the technological factor and adding natural capital to become the inputs of the function (human capital, physical capital, intellectual capital, and natural capital), so The cost of environmental damage was derived through the developed production function to reach an environmentally modified agricultural output, i.e. (sustainable agricultural growth). The study reached several conclusions, including the exclusion of the impact of environmental degradation from the production function and the calculation of the total environmentally-adjusted agricultural output.
Keywords: natural capital; human capital; intellectual capital; sustainable agricultural growth